(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2013)
The artist interview in this dossier is an example of collaborative work between an artist and a writer. It is a showcase of how popular culture can be re-appropriated. The interviewees are the co-creators of the card game Superstrumps developed to address the issue of stereotyping of women. In the interview, they recount the process of creating the game involving other women from their local community. This exemplifies how a strategy for resisting and reclaiming identities undermined by negative labelling is developed. Their views are strongly shaped by their feminist principles. The interview acknowledges the complex nature of identities, the challenge of media representation and the symbiotic relationship between media and audiences is revealed.